The Impact and Significance of Implementing the Income Cycle on MSMEs: A Case Study of Bakso Mbah Min Tangsel City - Raipah, Ainur; Apriyani, Via; Dyar Nugroho, Zefanya (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This research explores the impact and significance of implementing the income cycle on micro, small and medium enterprises (MSMEs), especially those represented by the Mbah Min Meatball Trader in Pamulang, South Tangerang. By using relevant theories and frameworks, this research aims to present a better understanding of how the implementation of the revenue cycle affects the financial, sustainability and development aspects of these MSMEs. An in-depth analysis of revenue management strategies, their impact on liquidity, profitability, and the business's ability to face market challenges is the main focus of this research. The expected result of this research is to provide a richer and deeper view of the benefits, challenges and implications of implementing the income cycle for MSMEs in the food industry, especially for the Mbah Min Meatball Trader. It is hoped that the practical implications of this research can contribute to improving financial management strategies and business growth for similar MSMEs and serve as a guide for relevant stakeholders in supporting the development of MSMEs in the region.